Home prices and inequality: Singapore versus other global superstar cities - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2015)
The Global City concept originates from the work of sociologist Saskia Sassen, which dates back to the 1980s. In an age of globalisation, division of labour is international in scope and production activities are distributed across the world. A global city is a significant point where the internationally oriented financial and producer services that make the global economy run choose to agglomerate.